2024
DOI: 10.1002/adma.202313835
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Multinary Metal Chalcogenide Bi0.4Sb1.6Te3 Nanocrystals for Efficient Potassium Storage

Longhai Zhang,
Jiatu Liu,
Yunming Zhai
et al.

Abstract: Multinary metal chalcogenides hold considerable promise for high‐energy potassium storage due to their numerous redox reactions. However, challenges arise from issues such as volume expansion and sluggish kinetics. Here, we present a design featuring a layered ternary Bi0.4Sb1.6Te3 anchored on graphene layers as a composite anode, where Bi atoms act as a lattice softening agent on Sb. Benefiting from the lattice arrangement in Bi0.4Sb1.6Te3 and structure, Bi0.4Sb1.6Te3/graphene exhibits a mitigated expansion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Some metal telluride materials have also been investigated as anode materials for PIBs. 402–404,571 Park et al 572 designed FeTe 2 –C nanospheres with a yolk–shell structure (Fig. 48a).…”
Section: Anode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some metal telluride materials have also been investigated as anode materials for PIBs. 402–404,571 Park et al 572 designed FeTe 2 –C nanospheres with a yolk–shell structure (Fig. 48a).…”
Section: Anode Materialsmentioning
confidence: 99%
“…Li et al 573 revealed that the dissolution and shuttle effect of the polytelluride intermediates (K x Te y ) in the electrolyte are responsible for the capacity decay of metal tellurides. Recently, Zhang et al 403 designed layered ternary Bi 0.4 Sb 1.6 Te 3 , in which Bi can be used as a lattice softener for Sb. As displayed in Fig.…”
Section: Anode Materialsmentioning
confidence: 99%